2011
DOI: 10.3109/09553002.2012.636138
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of bystander effect in suppression of the cytokine production induced by heavy-ion broad beams

Abstract: The suppression of cytokine production arose after irradiation with heavy-ions, and may also be induced in the surrounding non-irradiated cells via the bystander effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Irradiation of THP-1 derived macrophages with 0.5–20 Gy carbon ions (18.3 MeV/n, LET 108 keV/µm) has been shown to result in decreased TNF-α and IL-6 expression. Only extremely high doses (50 Gy) of carbon ions resulted in this study in an increased IL-6 expression (107). Irradiation of monocytes and macrophages with α-particles or accelerated carbon ions in therapeutic dose ranges (fractionated scheme) may therefore negatively modulate the immune response against tumor cells.…”
Section: Cytokines and Chemokinesmentioning
confidence: 77%
See 1 more Smart Citation
“…Irradiation of THP-1 derived macrophages with 0.5–20 Gy carbon ions (18.3 MeV/n, LET 108 keV/µm) has been shown to result in decreased TNF-α and IL-6 expression. Only extremely high doses (50 Gy) of carbon ions resulted in this study in an increased IL-6 expression (107). Irradiation of monocytes and macrophages with α-particles or accelerated carbon ions in therapeutic dose ranges (fractionated scheme) may therefore negatively modulate the immune response against tumor cells.…”
Section: Cytokines and Chemokinesmentioning
confidence: 77%
“…In coculture, U937 macrophages have been shown to secrete TNF-α and IL-1α (IL-1α not at high doses) after irradiation of NCI-H446 lung cancer cells with γ-rays ( 137 Cs Source, 8 Gy) but only TNF-α after irradiation with accelerated carbon ions (290 MeV/n, LET 13 keV/µm, 2 Gy) (99). Microbeam irradiation of 0.45% of a THP-1 derived macrophage population with 5 Gy carbon ions (18.3 MeV/n, LET 108 keV/µm) using a heavy ion microbeam resulted in significantly reduced expression of TNF-α and IL-6 (107). …”
Section: Cytokines and Chemokinesmentioning
confidence: 99%
“…Mutou-Yoshihara et al (2012) showed that suppression of cytokine production was induced in the surrounding non-irradiated cells via the bystander effect (Mutou-Yoshihara et al, 2012). Bystander responses have been measured after exposures as low as a single proton or helium ion delivered to an individual cell.…”
Section: Bystander Effectmentioning
confidence: 99%
“…Monocites of human immune cell line THP-1 were differentiated to macrophages, and, thereafter, a 0.45% fraction of the cell population was irradiated with a carbon ion microbeam. Assays of cytokine production after irradiation revealed that the production of TNF-α and IL-6 were suppressed by the bystander effect [41].…”
Section: Programmed Matrix Irradiation Without Targeting Specific Cellsmentioning
confidence: 99%